FGFR2-Rearrangement in Intrahepatic and Extrahepatic Cholangiocarcinoma and Prognostic Analysis - Guo J; Chen F; Li J; Xi Y (International Journal of General Medicine)
Jianghong Guo,1,* Fengxin Chen,2,* Jie Li,3 Yanfeng Xi1 1Department of Pathology, Cancer Hospital Affiliated to Shanxi Medical University, Shanxi Province Cancer Hospital, Shanxi Hospital Affiliated to Cancer Hospital, Chinese Academy of Medical Sciences, Taiyuan, Shanxi, People’s Republic of China; 2School of Basic Medicine, Shanxi Medical University, Taiyuan, Shanxi, People’s Republic of China; 3Customer Care (North I), Roche Diagnostics (ShanghaI) Limited, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yanfeng Xi, Email xiyanfeng1998@163.comAim: To investigate the clinicopathological features and prognostic factors of intrahepatic and extrahepatic cholangiocarcinoma.Methods: Clinicopathological and follow-up data of 328 cholangiocarcinoma patients treated at Shanxi Cancer Hospital from November 7, 2016, to August 11, 2021, were retrospectively reviewed. All samples were tested for Fibroblast growth factor receptor 2 (FGFR2) fusion by FISH. The expression of the proliferative marker Ki67 in patients with intrahepatic cholangiocarcinomas (iCCA) was evaluated by immunohistochemistry. All patients were followed up from the date of surgery to the time of death or August 31, 2023. Pathological specimens from patients with recurrence were collected and FGFR2 was tested again.Results: The positivity rates for FGFR2 fusion in intrahepatic, perihilar, and distal cholangiocarcinomas were 15%, 2.73%, and 1.69%, respectively. The chi-square test showed that tumor diameter, perineural invasion, complications, and FGFR2 fusion were statistically significant. Immunohistochemistry showed that patients with low expression of Ki67 accounted for 30% of iCCA, low expression of Ki67 and FGFR2 fusion was statistically significant. Relapse specimens were collected from 13 patients, and FISH showed that the expression of FGFR2 was consistent with that of the primary lesion. Multivariate analysis showed that lymph node metastasis was an independent factor for the prognosis of cholangiocarcinoma (P< 0.05).Conclusion: CCA is an aggressive tumor with high mortality and low survival rates, especially for perihilar cholangiocarcinoma (pCCA). Therefore, it is necessary to understand the clinicopathological features and prognostic factors of iCCA, pCCA and distal cholangiocarcinoma (dCCA). In addition, lymph node status is likely to be an independent and important prognostic factor.Keywords: cholangiocarcinoma, FGFR2, prognosis